Self-Healing Hydrogels: From Synthesis to Multiple Applications - Yin, Hongyan; Liu, Fangfei; Abdiryim, Tursun; Liu, Xiong (ACS materials letters, 2023)
Due to the good reliability and long-term stability, self-healing hydrogels have emerged as promising soft materials for tissue engineering, smart wearable sensors, bioelectronics, and energy storage devices. The self-healing mechanism depends on reversible chemical or physical cross-linking interactions. Self-healing hydrogels with fascinating features (including mechanical performances, biocompatibility, conductivity, antibacterial ability, responsiveness, etc.) are being designed and developed according to the practical application requirements. In this review, the recent progress on self-healing hydrogels in their synthesis strategies and multiple applications is summarized. Their synthesis strategies involve reversible chemical or physical cross-linking processes or a combination of the two. Their recent applications include flexible strain sensors, supercapacitors, actuators, adhesives, wound healing, drug delivery, tumor treatment, 3D printing, etc. Finally, the current challenges, future development, and opportunities for self-healing hydrogels are discussed.